2015
DOI: 10.1056/nejmoa1415921
|View full text |Cite
|
Sign up to set email alerts
|

Troponin and Cardiac Events in Stable Ischemic Heart Disease and Diabetes

Abstract: BACKGROUND Cardiac troponin concentrations are used to identify patients who would benefit from urgent revascularization for acute coronary syndromes. We hypothesized that they might be used in patients with stable ischemic heart disease to identify those at high risk for cardiovascular events who might also benefit from prompt coronary revascularization. METHODS We measured the cardiac troponin T concentration at baseline with a high-sensitivity assay in 2285 patients who had both type 2 diabetes and stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
148
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 241 publications
(167 citation statements)
references
References 25 publications
10
148
1
8
Order By: Relevance
“…Higher proportions have been reported in other cohorts (eg, 39% in the BARI 2D [Bypass Angioplasty Revascularization Investigation 2 Diabetes] trial) 10. In patients with diabetes mellitus with and without established cardiovascular disease, cardiac troponin concentrations are a significant predictor of myocardial infarction, stroke, heart failure, and cardiovascular death 9, 10, 23, 24. As a result, there is considerable interest in identifying treatment strategies that might modify troponin concentrations and thus confer cardiovascular benefit.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Higher proportions have been reported in other cohorts (eg, 39% in the BARI 2D [Bypass Angioplasty Revascularization Investigation 2 Diabetes] trial) 10. In patients with diabetes mellitus with and without established cardiovascular disease, cardiac troponin concentrations are a significant predictor of myocardial infarction, stroke, heart failure, and cardiovascular death 9, 10, 23, 24. As a result, there is considerable interest in identifying treatment strategies that might modify troponin concentrations and thus confer cardiovascular benefit.…”
Section: Discussionmentioning
confidence: 76%
“…As a result, there is considerable interest in identifying treatment strategies that might modify troponin concentrations and thus confer cardiovascular benefit. Our data suggest that glucose control with either insulin glargine, metformin, or the combination, at least over the relatively short‐term follow‐up of this trial, might be added to the list of interventions (including coronary revascularization and statin therapy) that do not appear to lead to clinically meaningful reductions in troponin concentrations 10, 25…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, Everett et al 7. reported that using Bypass Angiography Revascularization Investigation in Type 2 Diabetes trial data, the cardiac troponin T concentration is an independent predictor of death from cardiovascular causes, myocardial infraction or stroke in patients who had both type 2 diabetes and stable ischemic heart disease.…”
Section: Troponin T In Stable Cad and Diabetesmentioning
confidence: 99%